A revision of Afrotropical Asceua (Araneae, Zodariidae), ant-eating spiders with puzzling distributions - Rudy Jocqué; Arnaud Henrard (African Invertebrates, 2024)
The Afrotropical representatives of the zodariid spider genus Asceua Thorell, 1889 are revised. Apart from the known species A. radiosa Jocqué, 1986 (Comoros, Mayotte) and A. lejeunei Jocqué, 1991 (DR Congo, Ethiopia, Ghana, Guinea, Ivory Coast, Nigeria), six new species are recognized and described: A. arborivaga sp. nov. (♀, Guinea), A. foordi sp. nov., (♂♀, DR Congo, Guinea, South Africa), A. incensa sp. nov. (♂♀, DR Congo), A. luki sp. nov. (♂♀, DR Congo), A. palustris sp. nov. (♀, DR Congo) and A. ventrofigurata sp. nov. (♂♀, Tanzania). A key to the species is provided. Some of the species have a very large distribution, which is unusual in the Zodariidae. The phenomenon is probably linked to the canopy dwelling behaviour, which appears common in the genus but unique for this spider family.